Vivian (Forbes) Osterhaut (left) and her mother, Irene (Matthews) Forbes standing in front of the Forbes house - Forbes Family (1935)
Cataloguer's title. Dr. C.A. Forbes, son of Dr. R.E. Forbes and Elizabeth (Cowan) Forbes, married Irene (Matthews) Forbes, daughter of William Matthews and Julia (Sweetman) Matthews, in September, 1914. They had four children: Kathleen (born 1916), Vivian (born 1918), Clive (born 1921) and Lloyd (born 1924). Vivian (Forbes) Osterhaut married Douglas Osterhaut and had a son named Robert. The Forbes Family Photograph Collection contains 449 family photos of Dr. Robert E. Forbes and his son, Dr. C.A. Forbes, both physicians who collectively served Bonavista and nearby communities for over 80 years from ca. 1874 to 1955. Most of the photos are in albums, although they have been digitized as separate items, and are predominantly from the 20th Century. Many of the photos from the 1940s-50s are of two of Dr. C.A. Forbes' daughters, Vivian (Forbes) Osterhaut and Kathleen (Forbes) Deir, as well as Kathleen's husband Jack Deir who served in the Royal Canadian Army Medical Corps during World War II. A small number of images appear to date from the late 19th Century and include coverage of the family of Irene Matthews, wife of Dr. C.A. Forbes.